2011
DOI: 10.1111/j.1440-1827.2011.02735.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of invasive micropapillary carcinoma component in invasive breast carcinoma

Abstract: Invasive micropapillary carcinoma (IMP) of the breast is a rare variant of invasive breast carcinoma and most cases of IMP are associated with nodal metastasis and lymphatic invasion. Lesions composed of an IMP component alone are rare and almost always coexist with other pathological components. However, few reports have documented IMP along with its proportion and the coexistent pathological type. We analyzed the total 486 breast cancer lesions operated in our hospital in 1998. We classified the lesions into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 14 publications
6
25
0
Order By: Relevance
“…However, no consensus has yet been reached on the proportion of the IMPC component in a tumor that is required for its pathological diagnosis [13]. In addition, previous studies did not find a direct correlation between the ratio of the IMPC component and either lymph node involvement or survival [9], [17]. Furthermore, pathology data addressing histological grade and Ki-67 were excluded from the current analysis, but these variables may have an effect on survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no consensus has yet been reached on the proportion of the IMPC component in a tumor that is required for its pathological diagnosis [13]. In addition, previous studies did not find a direct correlation between the ratio of the IMPC component and either lymph node involvement or survival [9], [17]. Furthermore, pathology data addressing histological grade and Ki-67 were excluded from the current analysis, but these variables may have an effect on survival.…”
Section: Discussionmentioning
confidence: 99%
“…This carcinoma has been reported to exhibit lymphovascular invasion, lymph node metastasis, local recurrence and distant metastasis at relatively high frequencies, thus exhibiting a more aggressive behavior than invasive ductal carcinoma (IDC) [2], [3]. The rate of incidence of IMPC of the breast has been reported to range from 1.0–8.4% [4], [5], [6], [7], [8], [9], [10]. Due to the low incidence of this breast cancer variant, most studies examining IMPC have small sample sizes; the clinico-pathological characteristics and the clinical prognostic factors of invasive micropapillary carcinoma are therefore not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…7 The status of the HER2/neu protein expression or gene amplification in IMPC is not consistent in literature. Some studies showed HER2/ neu þ rates between approximately 10% and 30%, [14][15][16]23,24 whereas others reported between approximately 50% and 80%. 34,38,41,44 Regarding the molecular classification, more cases of IMPC fall into the luminal A and luminal B subtypes than they do with IDC-NOS.…”
Section: Immunophenotypementioning
confidence: 99%
“…7,[14][15][16][17]23,24,[37][38][39][40][41][42][43] One study of 624 patients with IMPC revealed a poor prognosis in the patients who had a tumor lacking in estrogen receptor expression. 7 The status of the HER2/neu protein expression or gene amplification in IMPC is not consistent in literature.…”
Section: Immunophenotypementioning
confidence: 99%
“…In addition, similar morphological characteristics of MPC are rarely detected in other non-ovarian sites, such as the breast, urinary bladder, lung, parotid glands and colon (27). In anatomical locations other than the ovaries, MPC exhibits an aggressive course and generally accompanies the primary neoplasm of the organ of its origin (2).…”
Section: Introductionmentioning
confidence: 96%